Microsatellite markers for the giant kelp macrocystis pyrifera - Alberto, F. (2014)
We report the isolation and characterization of 16 microsatellite loci to study the population genetics of the giant kelp, Macrocystis pyrifera. Markers were obtained by screening a genomic library enriched for microsatellite motifs. Of the 37 primer pairs defined, 16 amplified clean polymorphic microsatellites and are described. These loci identified a number of alleles ranging from three to forty (mean = 16.5, and gene diversity ranging from 0.469 to 0.930 (mean = 0.774). The isolation and characterization of these highly polymorphic markers will greatly benefit much needed studies on the molecular ecology of this important macroalga.